The Australian and New Zealand Journal of Obstetrics and Gynaecology (ANZJOG) Vol.56 No.1 February 2016 - Redaksi (Wiley-Blackwell, 2016)
- Noninvasive prenatal testing in routine clinical practice- An audit of NIPT and combined fist-trimester screening in an unselected Australian population - First trimester screening cut-offs for noninvasive prenatal testing as a contingent screen: Balancing detection and screen-positive rates for trisomy 21 Impact of the new IADPSG gestational diabetes diagnostic criteria on pregnancy outcomes in Western Australia -...